RETRACTED: Product Quality, Brand Image on Purchasing Decisions Through Purchase Intention of Private Label Products at Alfamart Outlets in Depok City Area - Chindera Kasih; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze the relationship between product quality, brand image on purchasing decisions through buying interest. In order for sales strategies conducted by Alfamart can also increase sales, reinforced with product quality and brand image. The result of the research used primary data in the form of questionnaire to 109 responder which is Alfamart customer who is shopping or have experience to buy private label product Alfamart with Structural Equation Modeling (SEM) method result show that there is no simultaneous relationship between brand image and purchase decision. There is a positive and significant influence between product quality and purchasing decision through buying interest indicating that higher product quality can increase buying interest so that purchasing decision will also increase.